Exercise as part of anxiety coping management in the Covid-19 pandemic era - Denny Agustiningsih; Rakhmat Ari Wibowo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Containment effort in the COVID-19 pandemic could disrupt circadian rhythms which play an essential role in the development of mood and anxiety disorders. Exercise is one of several recommendations for anxiety coping during the COVID-19 pandemic. However, not every person has a similar response to an exercise stimulus and gets the same optimal benefits. For the best exercise results, we must consider individual needs and capacities, including circadian rhythm, in determining the exercise dose. This review briefly summarizes the exercise’ mechanism as an anxiolytic through skeletal muscle-brain crosstalk and designing exercise program with the individual optimal dose as part of anxiety coping management in the COVID-19 pandemic situation, considering exercise as good stress and circadian rhythm.